Does obesity have an impact on the radiation exposure during lumbosacral transforaminal epidural steroid injections? Retrospective study (Annals of Medical Research, 2021)
Aim: To find out whether obesity or injection level have an impact on the amount of radiation exposure during fluoroscopy-guided lumbosacral transforaminal epidural steroid injections (TFESIs).Material and Methods: Patients aged 19-65 years who underwent lumbosacral transforaminal epidural steroid injection were retrospectively reviewed. Eighty-three patients with a mean age of 42.7±13.2 (19-65) years with signs and symptoms of unilateral lumbar radicular pain due to single level disc herniation were included. Subjects were categorized as normal weighted (18.5≤body mass index (BMI) ≤ 24.9), overweighed (25≤BMI30) and obese (BMI≥30) according to World Health Organization BMI criteria. All patients were given unilateral TFESIs, including39 (47%) L5, and 44 (53%) S1 level. Radiation exposure dose and procedure time was automatically measured by fluoroscope.Results: Radiation dosage increased significantly with increasing BMI (p=0.0001). No statistically significant differences were found when three groups’ procedure durations and NRS scores were compared (>0.05). The radiation dosages and procedure durations between the two different injection levels (L5 and S1) were not found to be statistically significant (>0.05). Conclusion: Obesity is associated with increased radiation exposure independent of procedure duration and the injection level.
Keywords: Body mass index; epidural injection; fluoroscopy; procedure time; kerma-area product